Integrasi Bahasa dan Budaya dalam Pembentukan Proses Kognitif Kompleks: Literatur Review - Aisyah Aisyah; Mega Kencana; Suci Fajrina (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The integration of language and culture plays a crucial role in shaping the complexity of human cognitive processes. Language acts not only as a means of conveying messages but also as a conceptual system that influences how individuals construct mental representations, process information, and reason. Culture, on the other hand, provides a set of values, norms, and thought patterns that shape attention, interpretation of experiences, and strategies for understanding the social world. A review of literature from the fields of linguistic relativity, cultural psychology, neurolinguistics, and cross-cultural cognition found that differences in language structure, bilingual experience, and cultural value orientations result in variations in perception, memory, and executive function. Neurocognitive findings indicate that the influence of language and culture is evident down to the level of brain activation. Furthermore, the sociocultural approach emphasizes the role of language as a mediating tool in the process of internalizing values ​​and developing higher-order cognitive abilities. Thus, human cognition is the result of a dynamic interaction between language, culture, and social experience.